2021
DOI: 10.1136/bmjspcare-2021-003220
|View full text |Cite
|
Sign up to set email alerts
|

Methadone and neuropathic cancer pain subcomponents: a prospective cohort pilot study

Abstract: Forty per cent of cancer pain associate neuropathic and nociceptive pain simultaneously, and refractory pain affects 15% of cancer pain. Methadone is an effective opioid in treating nociceptive pain and could have an effect on neuropathic pain. Uncertainty remains on its effects on the different subcomponents of neuropathic pain.ObjectivesTo identify which subcomponents of neuropathic cancer pain are addressed using methadone.MethodsAn observational prospective cohort study of palliative care inpatients after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Finally, switching from another opioid to methadone-a MOR agonist and N-methyl-D-aspartate (NMDA) antagonist-has been shown to improve pain scores in patients with NCP in a recently published prospective cohort pilot study. Allodynia and the pressure/squeezing sensations were the most markedly reduced [75]. Methadone's complex pharmacokinetic profile-most notably its long half-life-and its variable conversion ratio when switching from another opioid complicate its use in clinical practice [29].…”
Section: The Problem Of Neuropathic Painmentioning
confidence: 99%
“…Finally, switching from another opioid to methadone-a MOR agonist and N-methyl-D-aspartate (NMDA) antagonist-has been shown to improve pain scores in patients with NCP in a recently published prospective cohort pilot study. Allodynia and the pressure/squeezing sensations were the most markedly reduced [75]. Methadone's complex pharmacokinetic profile-most notably its long half-life-and its variable conversion ratio when switching from another opioid complicate its use in clinical practice [29].…”
Section: The Problem Of Neuropathic Painmentioning
confidence: 99%
“…Finally, switching from another opioid to methadone-a MOR agonist and N-methyl-D-aspartate (NMDA) antagonist-has been shown to improve pain scores in patients with NCP in a recently published prospective cohort pilot study. Allodynia and the pressure/squeezing sensations were the most markedly reduced [61]. Methadone's complex pharmacokinetic profile-most notably its long half-life-complicates its use in clinical practice [28].…”
Section: The Problem Of Neuropathic Feature In Cancer Painmentioning
confidence: 99%
“…Methadone is a synthetic opioid-receptor agonist and N-methyl-D-aspartate (NMDA) inhibitor [50]. A recent prospective cohort pilot study on patients with NCP indicated that methadone could significantly improve neuropathic pain through a targeted effect on allodynia and the pressure/squeezing component [51]. Due to its unpredictable very long half-life and risk of accumulation and toxicity, its use should be reserved to experienced clinicians [11,26].…”
Section: Opioidsmentioning
confidence: 99%